A cross-sectional study on knowledge, attitude and practice of infant feeding practices among reproductive age women attending outpatient department of obstetrics and gynecology in Dr. B. R. Ambedkar Medical College and Hospital, Bengaluru-45 - Jabeen, Bushra; Suryanarayana, S. P.; Puttaswamy, M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Adequate nutrition during infancy and early childhood is essential to ensure the growth, health, and development of children to their full potential. Lack of knowledge, wrong attitude and faulty practices among mothers in some aspects of infant feeding can lead to infant mortality. Thus, appropriate infant feeding practices and following recommended practice of exclusive breastfeeding could help in improvement of health of child and mother and also improve IMR. The objective of the study was assessment of knowledge, attitude and practice of infant feeding practices among reproductive age women. Methods: An institutional based, descriptive cross sectional study was conducted among reproductive age group (15 to 49 years) women attending OPD of OBGY department for various reasons. A semi structured questionnaire along with software tools like EpiInfo7, MS Excel and SPSS version 23 are used for data analysis. Results: A total of 98.5% of women consider breast milk as best nutrition and 77% were aware regarding exclusive breastfeeding. Weaning was most commonly started with mashed cereals (68.5%) with other food items at lower percentage. Participants are aware that breastfeeding is beneficial to both mother and child, and should not be avoided in any condition unless advised by treating doctor. Conclusions: Through the mothers under study had adequate knowledge regarding feeding practice but in this study it was observed that the appropriate practice worsens with increasing parity of mother.